Concept and general characteristic of corporate law (Journal of actual problems of jurisprudence, 2018)
In this article considered the problems of definition of corporate law as branch of law, legal science and a subject. The corporate law can be considered in two concepts. In broad concept, the corporate law is a set of precepts of law, on regulation of establishment of economic subjects and their activity, and also by determination of their legal status. In narrow concept, the corporate law designates system of rules which regulates internal legal relations, established by administration or the owner of property of corporate association.Key words: corporate law, a subject of corporate law, the corporate relations, branch of law.